Skutočne výnimoční - Srnková, Monika; Farkas, Rudolf; Kovács, Péter; Nagy, Attila, 1975-; Ruzsinszki, Zsolt; Szendrei, Tibor, 1963- (Kráľovstvo zvierat, 2019)
Navštívte s nami kráľovstvo zvierat a spoznajte jedinečné živočí